Initial anticoagulation in patients with pulmonary embolism: thrombolysis, unfractionated heparin, LMWH, fondaparinux, or DOACs? - Leentjens, Jenneke (Br J Clin Pharmacol, 2017)
The initial treatment of haemodynamically stable patients with pulmonary embolism (PE) has dramatically changed since the introduction of low molecular weight heparins (LMWHs). With the recent discovery of the direct oral anticoagulant drugs (DOACs), initial treatment of PE will be simplified even further. In several large clinical trials it has been demonstrated that DOACs are not inferior to standard therapy for the initial treatment of PE, and because of their practicability they are becoming the agents of first choice. However, many relative contraindications to DOACs were exclusion criteria in the clinical trials. Therefore, LMWHs will continue to play an important role in initial PE treatment and in some cases there still is a role for unfractionated heparin (UFH). In this review we will give an overview of the biophysical, pharmacokinetic and pharmacodynamic properties of anticoagulants currently available for the initial management of PE. In addition, we will provide a comprehensive overview of the indications for the use of UFH, LMWHs and DOACs in the initial management of PE from a pharmacokinetic/‐dynamic point of view.